Toward a pro-poor forest science - Kaimowitz, D. (2002)
Two distinct visions of tropical forests co-exist in the scientific literature. One is more neo-Malthusian. The other is more pro-poor. The evidence increasingly favours the latter, although many uncertainties remain. The pro-poor literature emphasises that poor families create and manage forests as well as destroy them, that the forests and the communities have evolved together, and that many forestry regulations and conservation initiatives hurt the poor without helping the forest. For those that support a more pro-poor vision, the challenge is to find ways to reach broader audiences with their message. That will require communicating in ways people can relate to and convincing them that they and the rural poor share many common interests.